Apixaban and dalteparin in active malignancy‐associated venous thromboembolism: The ADAM VTE trial - McBane, Robert D.; Wysokinski, Waldemar E.; Le‐Rademacher, Jennifer G.; Zemla, Tyler; Ashrani, Aneel; Tafur, Alfonso; Perepu, Usha; Anderson, Daniel; Gundabolu, Krishna; Kuzma, Charles; Perez Botero, Juliana; Leon Ferre, Roberto A.; et al. (Journal of thrombosis and haemostasis, 2020)
Background Low‐molecular‐weight heparin is the guideline‐endorsed treatment for cancer‐associated venous thromboembolism (VTE). While apixaban is approved for the treatment of acute VTE, limited data support its use in cancer patients. Objectives The primary outcome was major bleeding. Secondary outcomes included VTE recurrence and a composite of major plus clinically relevant non‐major bleeding (CRNMB). Patients/Methods Patients with cancer‐associated VTE were randomly assigned to receive either apixaban 10 mg twice daily for seven days followed by 5 mg twice daily for six months or subcutaneous dalteparin (200 IU/kg for one month followed by 150 IU/kg once daily). Results Of 300 patients randomized, 287 were included in the primary analysis. Metastatic disease was present in 66% of subjects; 74% were receiving concurrent chemotherapy. Major bleeding occurred in 0% of 145 patients receiving apixaban, compared with 1.4% of 142 patients receiving dalteparin [P = .138; hazard ratio (HR) not estimable because of 0 bleeding event in apixaban group]. Recurrent VTE occurred in 0.7% of apixaban, compared to 6.3% of dalteparin patients [HR 0.099, 95% confidence interval [CI], 0.013‐0.780, P = .0281). Major bleeding or CRNMB rates were 6% for both groups. Conclusions Oral apixaban was associated with low major bleeding and VTE recurrence rates for the treatment of VTE in cancer patients.